Biochemical profile of term neonates with perinatal asphyxia and their correlation with severity of asphyxia - Sachin V. Bhoye; Neha D. Bhongale; Rohit M. Thorat; Poonam A. Wade (Journal of Family Medicine and Primary Care)
Background: Birth asphyxia is a major cause of neonatal mortality and neurological morbidity. This study was aimed to determine biochemical (sodium, potassium, and calcium) abnormalities and their correlation across different severities of perinatal asphyxia in term neonates. Methods: This observational analytical study was conducted in term neonates with perinatal asphyxia admitted at the neonatal intensive care unit of a tertiary care centre for a period of 18 months. Blood collection was done at baseline, 24 hours, and 48 hours of treatment to evaluate electrolyte abnormalities. The abnormality in serum electrolytes was correlated across different stages of hypoxic ischaemic encephalopathy (HIE) as per severity and at different time intervals. Results: A total of 74 neonates were included in the study and classified into HIE stage 1 (n = 37), stage 2 (n = 18), and stage 3 (n = 19). At baseline, hyponatremia, hyperkalaemia, and hypocalaemia were observed in 36.5% (n = 27), 20.3% (n = 15), and 10.8% (n = 8), respectively. The difference between mean serum sodium (p: 0.007), potassium (P: 0.004), and calcium levels (p: 0.001) at baseline in stage 1 and stage 3 was statistically significant. The degree of hyponatremia and hyperkalaemia was more and statistically significant as per increasing severity of HIE. All the deaths (n = 6.8.1%) belonged to stage 3 of HIE. Conclusion: The degree of hyponatremia, hypocalaemia, and hyperkalaemia in the asphyxiated newborns correlated with the severity of birth asphyxia. The mortality rate was greater in asphyxiated neonates with severe HIE and electrolyte abnormality. Effective perinatal care and meticulous management of dyselectrolytemia are crucial for improving neonatal outcomes.